A socio-economic model of sales tax compliance - Ahmad Farhan Alshira'h; Moh'd Alsqour; Abdalwali Lutfi; Adi Alsyouf; Malek Alshirah (Economies, 2020)
Tax compliance is an issue that can be traced back to the introduction of taxes, which is the reason such compliance remains a significant topic in the current literature of academia and practice. Prior studies on the topic of tax compliance or non-compliance can be categorized into two, namely economic and social/psychological theories. In a more serious note, tax evasion has remained a key issue among governments all over the globe, with Jordan being no exception. Jordan has undertaken different fiscal measures to increase compliance in the domestic front in the past decades, but based on annual reports, the country is still experiencing a considerable increase in net public debt and fiscal deficit that can be traced back to the increased tax non-compliance rate. This is specifically true in the case of sales tax in Jordan. To compound the matter further, literature concerning the determinants of sales tax compliance as well as other determinants that drive non-compliance is still scarce, with a universal tax compliance model able to explain the issue with clarity still being elusive. Hence, this work proposed the determinants of sales tax compliance in the context of small and medium-sized enterprises (SMEs) in Jordan, extending Fischer's model of tax compliance, and adding the moderating role of tax knowledge and direct effect of tax service quality. This study proposed a model encapsulating the social, psychological and economic factors to provide insight into the sales tax compliance of Jordanian SMEs.
Keywords: C34; H57; E70; M45; 330; Fischer's model; sales tax compliance; tax knowledge; tax service quality